2021
DOI: 10.26529/cepsj.1108
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Assessment and Feedback Practices in Finland’s Foreign Language Classes During the Covid-19 Pandemic

Abstract: In this paper, we examine how the Covid-19 pandemic affected the quality of teachers’ assessment and feedback in Finland’s foreign language classes during the remote teaching period in spring 2020. Multifaceted assessment and feedback practices are underscored in Finland’s core curricula, forming a focal aspect of learning. Therefore, we studied teachers’ perceptions of their assessment and feedback practices at different school levels during the remote teaching period and how they considered the remote teachi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…In our literature review, we found that an approach that overlooks this underlying context of events in the interpretations of results, and is largely enthusiastic about what technology makes possible, is very common, and that researchers point out in their conclusions, among other things, that teachers could be better trained to work with ICT (e.g., Anderson, 2021;Karataş et al, 2021;Korhonen et al, 2021;Mäkipää et al, 2021). These demonstrations turn technology, which is a means, into an end.…”
Section: Theoretical Basis Of the Researchmentioning
confidence: 99%
“…In our literature review, we found that an approach that overlooks this underlying context of events in the interpretations of results, and is largely enthusiastic about what technology makes possible, is very common, and that researchers point out in their conclusions, among other things, that teachers could be better trained to work with ICT (e.g., Anderson, 2021;Karataş et al, 2021;Korhonen et al, 2021;Mäkipää et al, 2021). These demonstrations turn technology, which is a means, into an end.…”
Section: Theoretical Basis Of the Researchmentioning
confidence: 99%
“…In terms of assessment, closed-book exams at the end of the study unit were not recommended; instead, teachers should opt for more flexible assessment practices [25]. Even though teachers in higher education were not prepared for online assessment, they have created innovative assessment practices that increase authenticity [26], and in general, teachers feel that their assessment has been reliable [5]. In the emergency remote teaching framework, assessment plays a major role, but teachers first need to inquire about resources, after which they design pertinent assessment practices [10].…”
Section: Emergency Remote Teaching and Assessment In Online Contextsmentioning
confidence: 99%
“…In Finland, remote teaching during the COVID-19 pandemic has been investigated from a range of perspectives. For example, previous research has focused on language teachers' assessment and feedback practices [5], academic achievement in physics and chemistry [6], and comparisons between Thai and Finnish higher education students [7]. These studies show that students in Finland faced challenges with time management [6] but not particularly with technical issues [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, teachers' online feedback can stimulate language development (Ene & Upton, 2014). Previous research on teachers suggests that feedback practices in foreign language emergency remote teaching have changed (Mäkipää et al, 2021a;Panadero et al, 2022). Hence, it is crucial to examine feedback in emergency remote teaching from students' perspectives, to revise feedback practices and to promote educational equity.…”
Section: Distance Education and Emergency Remote Teachingmentioning
confidence: 99%